ANALISIS PENGGUNAAN KEIGO DALAM DRAMA DI MUSIM GUGUR KOUNODORI SEASON 1 - Prahesti, Natya Yoga (Universitas Negeri Semarang, 2020)
As a Japanese language learner requires mastering the language of respect (keigo) which is not only from learning in the classroom but can through television dramas containing respectful language to be used as learning models can be used by Japanese language learners. One of them is in the drama titled